Kredit Usaha Rakyat dan Perkembangan UMKM di Kabupaten Simeulue Pasca Covid-19 - Syamsuar, Syamsuar; Ikhwan, M.; Sabi, Marchi Raida (Faculty of Islamic Economics and Business, Madura Islamic State University, 2022)
Abstract : People's Business Credit (KUR) is a form of government program in increasing access to financing for Micro Small and Medium Enterprises (MSMEs) with low-interest rates, this program is channeled through financial institutions with guarantee patterns. KUR funds are given to people who have productive businesses with varying amounts to the business conditions involved, but during the covid-19 pandemic, the MSME sector also experienced the difficulty of installment returns, so this study was conducted to answer two fundamental questions, are: how KUR funds in the review of sharia economic law and how the fate of MSMEs during the covid-19 pandemic in Simeulue Regency. This research is qualitative research and data collection techniques using observation, interview, and documentation, while data analysis uses descriptive techniques. Based on the results of research it can be concluded that in the incarnation of Sharia economic law regarding KUR there are two opinions, first declaring the law haram because it includes riba, while the second opinion asserts that the legal KUR can and does not include riba. The difference lies in whether or not the interest of the KUR. Then the influence of covid-19 on MSMEs in Simeulue Regency is bad for the development of community businesses due to the lack of buyer interest so that the weakening of their income and the effect on delayed installment payments beyond the due date.